2018
DOI: 10.1177/0267658318764535
|View full text |Cite
|
Sign up to set email alerts
|

Preserved morphological processing in heritage speakers: A masked priming study on Turkish

Abstract: In a masked morphological priming experiment, we compared the processing of derived and inflected morphologically complex Turkish words in heritage speakers of Turkish living in Berlin and in native speakers of Turkish raised and living in Turkey. The results show significant derivational and inflectional priming effects of a similar magnitude in the heritage group and the control group. For both participant groups, semantic and orthographic control conditions indicate that these priming effects are genuinely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
1
11
2
Order By: Relevance
“…For our HS group, we obtained a semantic priming effect whereas Jacob et al (2019) did not for their HS group; Jacob and Kırkıcı (2016) did not have a semantic condition in their study. We believe this discrepancy between our results and those of Jacob et al (2019) is due to differences in the experimental materials of the two studies. Perea and Rosa (2002) reported that word pairs which are truly semantically related through antonymy/synonymy yield significantly higher semantic relatedness scores than word pairs that are just associated in meaning.…”
Section: Comparisons To Previous Researchcontrasting
confidence: 96%
See 4 more Smart Citations
“…For our HS group, we obtained a semantic priming effect whereas Jacob et al (2019) did not for their HS group; Jacob and Kırkıcı (2016) did not have a semantic condition in their study. We believe this discrepancy between our results and those of Jacob et al (2019) is due to differences in the experimental materials of the two studies. Perea and Rosa (2002) reported that word pairs which are truly semantically related through antonymy/synonymy yield significantly higher semantic relatedness scores than word pairs that are just associated in meaning.…”
Section: Comparisons To Previous Researchcontrasting
confidence: 96%
“…For the non-heritage CTR group we found morphological priming effects that are clearly dissociable from facilitation due to orthographic or semantic prime-target overlap, which is in line with the results of many previous masked-priming studies with L1 speakers of different languages (Marslen-Wilson, 2007). For Turkish HS, there are two previous masked-priming studies (Jacob & Kırkıcı, 2016;Jacob et al, 2019) to which we can compare our findings. One outcome that has been obtained in the two previous studies as well as in our study is the significant priming effect for regularly inflected word forms.…”
Section: Comparisons To Previous Researchsupporting
confidence: 91%
See 3 more Smart Citations